DNA computing based stream cipher for internet of things using MQTT protocol - Noor A. Hussein; Mohamed Ibrahim Shujaa (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Internet of Things (IoT) is a rapidly developing technology that enables “devices” to communicate and share information amongst them without human control. The devices have the features of internet connectivity and networking. Due to the increasing demands of a secure environment in IoT application, security has become a crucial aspect on which researchers have been increasingly focused. Connecting devices to the internet can facilitate intruders to attack devices as they can access the data from anywhere in the globe. In this work, an encryption–decryption process-based stream cipher has been used. The messages between IoT nodes were encrypted using One Time Pad (OTP) and DNA computing. Furthermore, the required key sequence was generated using a linear feedback shift register (LFSR) as a pseudo number key generator. This key sequence was combined to generate a unique key for each message. The algorithm was implemented using source python and tested on a Raspberry pi under Linux open operation system.